The effects of irrelevant stimuli: 1. The time course of stimulus-stimulus and stimulus-response consistency effects with Stroop-like stimuli, Simon-like tasks, and their factorial combinations. - Kornblum, Sylvan; Stevens, Gregory T.; Whipple, Anthony (Journal of Experimental Psychology. Human Perception & Performance, 1999)
The effects of Simon- and Stroop-like stimuli are examined in isolation and in factorial combinations with different delays between the presentation of the irrelevant and the relevant stimuli. The effects of irrelevant stimuli have different time courses depending on whether they overlap with the relevant stimulus (stimulus–stimulus overlap, Dimensional Overlap DO Type 4) or with the response (stimulus–response overlap, DO Type 3). A new, computational, parallel distributed processing (PDP)–type model, DO'97, is presented that is based on the original DO model (S. Kornblum, 1994; S. Kornblum, T. Hasbroucq, & A. Osman, 1990), and it postulates a nonmonotone irrelevant stimulus activation function in addition to 2 temporally ordered, serial, nonindependent stages: a stimulus processing stage and a response production stage. DO'97 is able to simulate the temporal dynamic characteristics of the processes, with good fits to the empirical data of this study and other published studies, at the level of means, variances, and distributional plots. Reprinted by permission of the publisher.